2014
DOI: 10.1111/cen.12595
|View full text |Cite
|
Sign up to set email alerts
|

Lack of impact of angiotensin‐converting enzyme gene polymorphism and salt intake on insulin resistance and limb blood flow

Abstract: Reported differences in insulin sensitivity between ACE genotypes were not found in this study under strict regulation of sodium intake. Insulin sensitivity was also unaffected in either group by sodium loading. ACE genotype and salt status do not impact on insulin sensitivity through changes in limb blood flow during hyperinsulinaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…After seven days of low, compared to seven days of high salt intake, insulin-mediated whole-body glucose disposal decreased, which is in contrast with several animal studies [73][74][75][76][77][78][79] . Similar findings, however, have been obtained in a number of controlled experiments performed in healthy 80,81 , hypertensive 82 , and hypertension-prone 83 individuals, whereas other investigators, using a comparable set-up, did not observe an effect of changes in salt intake on metabolic insulin signalling in healthy individuals 84 and participants with type 2 diabetes 85 . Only one study has demonstrated improved insulin sensitivity after salt restriction in eight obese and hypertensive individuals 86 .…”
Section: Effects Of Weight Loss and Changes In Salt Intake On Aldoste...supporting
confidence: 85%
See 2 more Smart Citations
“…After seven days of low, compared to seven days of high salt intake, insulin-mediated whole-body glucose disposal decreased, which is in contrast with several animal studies [73][74][75][76][77][78][79] . Similar findings, however, have been obtained in a number of controlled experiments performed in healthy 80,81 , hypertensive 82 , and hypertension-prone 83 individuals, whereas other investigators, using a comparable set-up, did not observe an effect of changes in salt intake on metabolic insulin signalling in healthy individuals 84 and participants with type 2 diabetes 85 . Only one study has demonstrated improved insulin sensitivity after salt restriction in eight obese and hypertensive individuals 86 .…”
Section: Effects Of Weight Loss and Changes In Salt Intake On Aldoste...supporting
confidence: 85%
“…Aldosterone is a steroid hormone that is mainly produced in the adrenal zona glomerulosa, and its levels are tightly regulated by AngII, extracellular [K + ] and ACTH 83 . So-called mineralocorticoid-releasing factors, derived from adipose tissue, have been suggested to increase adrenal aldosterone synthesis as well [84][85][86] , and adipocytes appeared to be capable of aldosterone production themselves 87 , which may at least partially explain the increase in circulating aldosterone observed in obese individuals 88 . It should be noted, however, that previous studies demonstrating elevated aldosterone levels in obesity, and a decrease following weight loss, have been performed in severely to morbidly [88][89][90][91] , and hypertensive overweight and obese individuals [92][93][94] .…”
Section: Aldosteronementioning
confidence: 99%
See 1 more Smart Citation